SINERGI IOT DAN SMART CONTRACTS DALAM ARSITEKTUR ERP BERBASIS BLOCKCHAIN: TINJAUAN LITERATUR SISTEMATIS - Samue Libert T; Totok Dewayanto (Diponegoro Journal of Accounting, 2026)
This research aims to analyze the synergy between the Internet of Things (IoT) and smart contracts in a blockchain-based Enterprise Resource Planning (ERP) architecture through a systematic literature review. The background of this research is based on the limitations of traditional ERP systems, which still face issues related to data security, information integrity, and the potential for fraud due to their centralized nature. The development of blockchain technology offers solutions through its characteristics of decentralization, transparency, and data immutability. Furthermore, IoT enables real-time data collection from its source, reducing manual input errors. This technological integration is expected to improve the quality of accounting information systems. This synergy also has the potential to strengthen a company's internal control. Therefore, this research is crucial for understanding the transformation of digital technology-based ERP systems. The research method used is a Systematic Literature Review (SLR), which examines various relevant scientific articles. The research process involves identifying, selecting, and analyzing literature based on specific criteria. Data is analyzed qualitatively to identify patterns and research gaps. This approach provides a comprehensive overview of technology integration in ERP. The results show that the integration of blockchain, IoT, and smart contracts can improve security, transparency, and operational efficiency. Smart contracts automate business processes, while IoT improves data accuracy. However, implementation still faces challenges such as system complexity and resource constraints.